Do Circumstances Matter For Earnings? An Empirical Evidence From Household Level Survey In Punjab (Pakistan) - ShahlaAkram; ZahidPervaiz; Jan, Sajjad Ahmad (The journal of contemporary issues in business and government, 2021)
This study investigates the role of circumstances and efforts in determining the income differences of individuals by using household-level data from the second wave of Multiple Indicator Cluster Survey (MICS) conducted in Punjab province of Pakistan. Education and work experience of the individuals have been used as proxy of efforts while education, region of residence, and wealth status of individuals’ fathers are used to indicate circumstances. Three different models have been used to estimate the effects of efforts and circumstances upon incomes of the individuals. The first model estimates the effects of indicators of efforts upon income of the individuals while the second model estimates the effects of indicators of circumstances upon income of individuals. The third model combines the indicators of efforts and circumstances into one equation and estimates their effects on individuals’ incomes.To cope with the possible problem of endogeneity and omitted variable bias, Monte Carlo simulation bootstrapping technique with 500 iterations has been used. The results show that both efforts and circumstances play an important role to determine income of the people in the province of Punjab.Education and working experience of individuals are positively and significantly related with their earnings. Similarly variables related with circumstances (father’s education, father’s region of residence and father’s wealth status) have also been found to be significantly related with income of individuals.